Sedimentological Influence on Physical Properties of a Tight Sandstone Reservoir: The Cretaceous Nenjiang Formation, Southern Songliao Basin, Northeast China - Wang, Jinkai; Fu, Jialin; Wang, Jieming; Zhao, Kai; Zhang, Jinliang; Liu, Jifu (Frontiers in Earth Science, 2021)
Abstract: The Nenjiang Formation, south of Songliao Basin, has many hydrocarbon bearing units, but currently the understanding of the distribution of viable reservoir sandstones is too limited to support a development strategy. Therefore, a detailed study on the sedimentary microfacies and reservoir properties has been completed in order to reduce uncertainty and improve subsurface predictions. Nine lithofacies and five lithofacies associations were identified supporting the development of a sedimentary model of a river-dominated delta front setting, which could be divided into four sedimentary environments: subaqueous distributary channel-fill, mouth bar, sand sheet, and interdistributary bay. The distribution sandbodies extend to the south in a tongue-like form, and they thin and pinch out. Finally, the influence of sedimentary process on properties was assessed by establishing the correlation between microfacies and reservoir physical parameters, such as porosity, permeability, pore radius, throat radius, and clay minerals. It is revealed that the correspondence between reservoir physical properties and microfacies types is strong; the physical properties of the subaqueous distributary channel and mouth bar are the best.